(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
ERP stands for enterprise resource planning, which is the integrated management of key business operations, which is typically done in real time and mediated by software and technology. Enterprise resource planning (ERP) is a type of business management software that consists of a set of integrated applications that allow a company to gather, store, manage, and understand data from a variety of business processes. Local or cloud-based enterprise resource planning (ERP) systems are available. Because information is accessible from any location with internet connection, cloud-based apps have gained in popularity in recent years. Using shared databases managed by a database management system, enterprise resource planning (ERP) gives an integrated and continually updated picture of fundamental business activities. ERP systems track business resources such as cash, raw materials, manufacturing capacity, and the status of business obligations such as orders, purchase orders, and payroll. The system’s applications distribute data among the many departments that provide it (manufacturing, purchasing, sales, accounting, and so on). Enterprise resource planning (ERP) handles links with external stakeholders and enables information flow across all corporate units. In this paper discuss the Enterprise resource planning (ERP), Intellectual Capital and Importance of Enterprise Resource Planning (ERP) in Increasing Intellectual Capital in Organisations.